2021
DOI: 10.1589/rika.36.717
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Prescribed Starting Position on the Range of Distribution of Forward Reach Distances in the Functional Reach Test

Abstract: To investigate the effect of controlled starting position condition on the forward reaching distance during Functional Reach Test (FRT). [Participants and Methods] Sixteen healthy males participated in this study. The range of distribution of the right acromion, greater trochanter, center of pressure, and forward reaching distance were analyzed in the controlled starting condition and uncontrolled starting condition during FRT. [Results] The range of distribution of the right acromion position, greater troch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…In both conditions, the right acromial process distribution range (ADR), great trochanter distribution range (GTDR), COP position distribution range (COPDR) in the start position, and RDDR were defined as the differences between the most anterior and posterior positions in the individual’s three trials 16 , 17 ) .…”
Section: Participants and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In both conditions, the right acromial process distribution range (ADR), great trochanter distribution range (GTDR), COP position distribution range (COPDR) in the start position, and RDDR were defined as the differences between the most anterior and posterior positions in the individual’s three trials 16 , 17 ) .…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Consequently, results have been inconsistent regarding the relationship between reach distance and SBA in older adults. One reason for the lack of consistent results may be that the start position in the FRT is typically not well controlled 15 , 16 , 17 ) . Duncan et al 18 ) reported that only the foot position was controlled as the start position in the FRT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that a CSSP is an important factor for accurately calculating the FoRD in an FRT. Conversely, it has been reported that there is no correlation between the FoRD and the anteroposterior MDCOP in the forward reach with the hip joint strategy adopted by Duncan et al 1 ) , regardless of whether the starting standing position was controlled 7 ) . The MDCOP is one of the indicators of the limits of stability in the standing position 8 ) and has been reported to be related to the SBA 3 ) .…”
Section: Introductionmentioning
confidence: 96%
“…Nishimura et al. 7 ) reported that the distribution range of the FoRD (DRFoRD) was reduced by a CSSP in the FRT. These results suggest that a CSSP is an important factor for accurately calculating the FoRD in an FRT.…”
Section: Introductionmentioning
confidence: 99%